Efficacy of morpholinium-methyl-triazolyl-thioacetate (thiotriazolin) for neurotrophic keratoconjunctivitis in long-term silicone hydrogel contact lens wearers (Ukrainian Journal of Ophthalmology, 2026)
Background: Vision correction with contact lenses offers some clear advantages as compared to correction with spectacles, but has some negative effect on the eye, too. Individuals wearing soft contact lenses (SCL) for years may develop neurotrophic keratoconjunctivitis that requires a long-term and mostly symptomatic treatment.Purpose: To compare the efficacy of different routes of morpholinium-methyl-triazolyl-thioacetate (thiotriazolin) administration for neurotrophic keratoconjunctivitis in patients wearing silicone hydrogel contact lenses for different periods of time.Materials and Methods: Two hundred and seventeen eyes of 112 patients with low or moderate myopia were examined and treated. These included 65 eyes of 33 patients wearing spectacles, and 159 eyes of 79 patients wearing SCL for long periods of time. SCL wearers were divided into subgroups depending on the treatment regimen and categorized depending on duration of SCL wear. Lactate dehydrogenase, glucose-6-phosphate dehydrogenase, succine dehydrogenase, and acid phosphatase activities in the tear film, and tear contents of glutathione, malondialdehyde and diene conjugates were examined.Results and Conclusions: Treatment with thiotriazolin statistically significantly decreased lipid peroxidation activity levels, with a reduced disruption of ocular surface membranes, and protected the ocular surface from oxidative stress.
Keywords: neurotrophic keratoconjunctivitis; morpholinium-methyl-triazolyl-thioacetate (thiotriazolin); lactate dehydrogenase; glucose-6-phosphate dehydrogenase; acid phosphatase; succine dehydrogenase; glutathione; malondialdehyde; diene conjugates